Transposition of reversed Ac element ends generates chromosome rearrangements in maize. - Zhang, Jianbo (2004)
In classical "cut-and-paste" transposition, transposons are excised from donor sites and inserted at new locations. We have identified an alternative pathway in which transposition involves the 5' end of an intact Ac element and the 3' end of a nearby terminally deleted fAc (fractured Ac). The Ac and fAc elements are inserted at the maize p1 locus on chromosome 1s in the same orientation; the adjacent ends of the separate elements are thus in reversed orientation with respect to each other and are separated by a distance of approximately 13 kb. Transposition involving the two ends in reversed orientation generates inversions, deletions, and a novel type of local rearrangement. The rearrangement breakpoints are bounded by the characteristic footprint or target site duplications typical of Ac transposition reactions. These results demonstrate a new intramolecular transposition mechanism by which transposons can greatly impact genome evolution.